ИНГЛИЗ ТИЛИНИ ЎРГАНИШ ЖАРАЁНИДА ТАЛАБАЛАРНИНГ МАДАНИЯТЛАРАРО АЛОҚАЛАРИНИ ТАКОМИЛЛАШТИРИШНИНГ ПЕДАГОГИК ШАРТЛАРИ - Менлимуратова, Э.А. (SCIENCE and SOCIETY, 2023)
The article discusses the pedagogical conditions for the development of intercultural relations among students, necessary for the development of foreign language competence among students, takes into account such factors as the needs and requirements of higher professional education, educational conditions.
Keywords: student; intercultural; English language; communication; language; consciousness; worldview; national; group; education; condition